European cross-country crime statistics, surveys and reports - Klima, Noël (European crime prevention monitor, 2012)
This report is a start up of a series of European Crime Prevention Monitor reports published every six months, presenting information on crime situations and crime trends based on statistics, surveys and reports. This first report presents findings from different international cross-country crime statistics, surveys and reports. A summary of some data, reports and on the major findings is outlined and presented with a focus on the 27 European Member States where possible. The aim of this report is to provide a quick and substantial, but selected overview of the situation and trends on crime and crime prevention in European Member States from the perspectives of the used data and literature. Target groups are local, national and European practitioners and policy makers. This report does not claim to be exhaustive. There are more statistics, surveys and reports which were not considered for this report. The data used has been published elsewhere and is not originally collected by the EUCPN. However, the information used in this report is analysed and presented in accordance with the needs of the target groups and the strategy of the EUCPN.